THE GROWTH AND YIELD OF PADDY CIHERANG PLANTED IN DRY AND WET SEASON AND FERTILLIZED WITH ORGANIC AND INORGANIC FERTILIZERS - Santosa, Mudji; Suryanto, Agus (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2015)
The study aiming to know the growth and yield of paddy Ciherang planted in dry and wet season and applicated with organic and inorganic fertilizers was conducted in paddy soil in Batu, East Java, 900 m asl. 220C with andosol soil type. A factorial randomized block design was applied to arrange the treatments of time of planting (dry and wet season) and the type of fertilizer used i.e.: 100 kg N ha-1 + 50 kg P2O5 ha-1 + 70 kg K2O ha-1, 50 kg N ha-1 + 25 kg P2O5 ha-1 + 35 kg K2O ha-1, 20 t ha-1 cow manure, and 10 t ha-1 cow manure. Each treatment replicated three times. The result showed tha the growth and yield of paddy Ciherang in dry seasons was higher than that in wet seasons. Plant height in dry seasons was 86.9 cm tall, Leaf Area Index (LAI) was 4.18, time of harvesting was 125 days after planting (DAP), and the grains yield was 9.84 t ha-1. The same characterstics of paddy Ciherang in wet seasons were 87.7 cm tall, with LAI 3.70, time of harvesting 105 DAP, and the grains yield 4.81 t ha-1.